Doping of amorphous and microcrystalline silicon films deposited at low substrate temperatures by hot-wire chemical vapor deposition - Alpuim, P. (2001)
The gas phase doping of amorphous (alpha -Si:H) and microcrystalline (muc-Si:H) silicon thin films deposited at substrate temperatures of 25 degreesC and 100 degreesC by hot-wire chemical vapor deposition is studied. Phosphine was used for n-type doping and diborane for p-type doping. The electronic and structural properties of the doped films are studied as functions of hydrogen dilution. Films were deposited on glass and polyethylene terephthalate. Similar dark conductivities, sigma (d), were obtained for the doped films deposited on either substrate. sigma (d) above 10(-6) Omega (-1) cm(-1) were obtained for a-Si:H films doped n-type at 25 degreesC and 100 degreesC (sigma (d)> 10(-4) Omega (-1) cm(-1)) and for alpha -Si:H doped p-type only at 100 degreesC. sigma (d), equal or above 10(-1) Omega (-1) cm(-1), were obtained for muc-Si:H doped p-type at 25 degreesC and 100 degreesC for Ac-Si:H doped n-type. only at 100 degreesC. Isochronal annealing at temperatures up to 200 degreesC reveals that, while the dopants are fully activated in microcrystalline samples, they are only partially activated in amorphous films deposited at a low substrate temperature.